A CASE SERIES OF EUCALYPTUS OIL-INDUCED SEIZURES - SHANMUGAM, SINDHU; I SAHAY, MELINA; GRACE RAJAN, PEARLSY; DK, SRIRAM; GEORGE, MELVIN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Eucalyptus oil (EO) is an essential oil which has been used as a traditional remedy in upper respiratory tract infection. It contains approximately 90% cineole and is readily available worldwide in over-the-counter cough drops, liniments, toothpaste, mouthwashes, cold preparations, and hair lice remover. EO-induced adverse drug reaction is rare in both adults and children. The signs and symptoms of EO poisoning are CNS depression, hypotension, tachycardia, epigastric pain, nausea, vomiting, and contact dermatitis. Symptom onset is usually rapid and resolves within 24 h. We report the case series of four adult patients with EO-induced seizure in India, who inhaled EO for common cold and presented to the critical care with single first attack of generalized tonic-clonic seizures. On further evaluation, none of them had a family background of seizures/febrile seizures. EEG and brain MRI were found to be normal in all patients. All the patients were managed with anti-epileptic drugs and standard supportive care. All medical practitioners should be aware of the toxic effects of EO, a common OTC medication used in Indian households. Warning labels may be attached on EO comprised products.